KORELASI RIBA,ZAKAT DAN SHODAQOH DALAM TEORI BATAS MUHAMMAD SYAHRUR - Ahmad Hamdani (MALIA: Journal of Islamic Banking and Finance, 2017)
Thisarticlewants to expose the thinking of a controversial Syrian thinker,Prof.Ir. Muhammad Syahrur about the correlation of usury, zakah and shodaqoh. The correlation between these three things to explain one of the forms of boundary theory he found. According to Syahrur usury and zakat contained in the theory of the sixth limit is "the maximum limit (positive) should not be passed and the lower limit (negative) may be passed". This restriction applies to the transition of wealth between people. These two limits consist of the maximum limit that should not be violated, namely usury and the minimum limit of zakat that can be exceeded. This form exceeds the minimum limit of a variety of alms. These two boundaries are in two regions: positive and negative regions, and midpoints in neutral positions denoted by zero. In practice, the positive maximum limit of usury, the neutral limit of interest-free loans and the minimum limit of negatives in the form of zakat and alms. According to Syahrur usury is divided into two forms that are related to borrowing and borrowing and borrowing. Syahrur argues that usury is the same as bank interest and he justifies bank interest as the modern banking mechanism that has been run for this.After describing Syahrur's thoughts, this paper provides some notes on the important points that need to be discussed further. Keywords:usury,zakah,shodaqoh